Predictors of use of direct oral anticoagulants in patients with venous thromboembolism: Findings from the Registro Informatizado Enfermedad Tromboembólica registry - Lorenzo, Alicia; Beroiz, Patricia; Ortiz, Salvador; del Toro, Jorge; Mazzolai, Lucia; Bura-Riviere, Alessandra; Visonà, Adriana; Verhamme, Peter; Di Micco, Pierpaolo; Camporese, Giuseppe; Sancho Bueso, Teresa; Monreal, Manuel; et al. (Frontiers in Medicine, 2022)
Background Current guidelines recommend the use of direct oral anticoagulants (DOACs) for patients with venous thromboembolism (VTE). However little is known about the use of DOACs in daily practice. Methods We used the RIETE registry to identify predictors of use of DOACs for initial and/or long-term therapy of VTE based on patient-related factors, institution-related factors or over time. Results Among 41,678 patients from March 2013 to September 2021, 12,286 (29%) used DOACs: for initial therapy 6,456; for long-term therapy 12,046. On multivariable analysis, independent predictors were: age < 65 years (odds ratio [OR]: 1.30; 95% CI: 1.23–1.38), body weight <50 kg (OR: 0.54; 95% CI: 0.45–0.65) or >120 kg (OR: 0.64; 95% CI: 0.53–0.77), initial VTE presentation as pulmonary embolism (OR: 1.18; 95% CI: 1.13–1.25), recent bleeding (OR: 0.53; 95% CI: 0.45–0.63), renal insufficiency (OR: 0.44; 95% CI: 0.38–0.51), liver cirrhosis (OR: 0.32; 95% CI: 0.20–0.52), thrombocytopenia (OR: 0.40; 95% CI: 0.34–0.49), atrial fibrillation (OR: 1.58; 95% CI: 1.42–1.75) and prior VTE (OR: 1.14; 95% CI: 1.06–1.22). The DOACs were more likely used in other European countries (OR: 8.97; 95% CI: 8.49–9.49), America (OR: 6.35; 95% CI: 5.67–7.11) or in other countries of the world (OR: 2.99; 95% CI: 2.70–3.31) than in Spain, and progressively increased from 2013–2015 to 2016–2018 (OR: 2.78; 95% CI: 2.62–2.95) and 2019–2021 (OR: 6.36; 95% CI: 5.95–6.80). Conclusion In this large multinational VTE registry, variations were observed in the use of DOACs according to patient or country factors, and over time. The safety, costs, and influence of the DOACs on VTE-related outcomes in daily practice warrant further investigation.